Parent-child Relationship in the Digital Era - Abu Hilal, Suzan Muhammad; El-Halaq, Iyad Saleem (Journal of Educational and Psychological Sciences, 2024)
This study aimed to identify the Parent-Child Relationship today, as it is considered one of the most Semitic and important human relations and it is also considered one of the important topics in the field of psychology, which many researchers have taken care of studying it. Despite the importance of the topic, it did not have the same importance at the level of Arab studies. The study highlights the understanding of the relationship between the child and his parents and focuses on healthy relationships and its role in promoting the mental, linguistic, and emotional development of the child, as well as addressing the concept of parents, parenthood in raising children, and its impact on the development of the child. The study also discusses the daily relationship between the child with his parents and focuses on the factors that contributed to the occurrence of many changes to that relationship in our time. At the end of this study, many practical methods and practices that contribute to strengthening the relationship between the child and his parents are being raised.
Keywords: the parent child relationship; parenting; parenthood; healthy relationship between the child and his parents